Multifunctional synthetic Bowman's membrane-stromal biomimetic for corneal reconstruction. (May 2020) - Wang, Xiaokun; Majumdar, Shoumyo; Soiberman, Uri; Webb, Joshua N.; Chung, Liam; Scarcelli, Giuliano; Elisseeff, Jennifer H.
Abstract: As the outermost layer of the eye, the cornea is vulnerable to physical and chemical trauma, which can result in loss of transparency and lead to corneal blindness. Given the global corneal donor shortage, there is an unmet need for biocompatible corneal substitutes that have high transparency, mechanical integrity and regenerative potentials. Herein we engineered a dual-layered collagen vitrigel containing biomimetic synthetic Bowman's membrane (sBM) and stromal layer (sSL). The sBM supported rapid epithelial cell migration, maturation and multilayer formation, and the sSL containing tissue-derived extracellular matrix (ECM) microparticles presented a biomimetic lamellar ultrastructure mimicking the native corneal stroma. The incorporation of tissue-derived microparticles in sSL layer significantly enhanced the mechanical properties and suturability of the implant without compromising the transparency after vitrification. In vivo performance of the vitrigel in a rabbit anterior lamellar keratoplasty model showed full re-epithelialization within 14 days and integration of the vitrigel with the host tissue stroma by day 30. The migrated epithelial cells formed functional multilayer with limbal stem cell marker p63 K14 expressed in the lower layer, epithelial marker K3 and K12 expressed through the layers and tight junction protein ZO-1 expressed by the multilayers. Corneal fibroblasts migrated into the implants to facilitate host/implant integration and corneal stromal regeneration. In summary, these results suggest that the multi-functional layers of this novel collagen vitrigel exhibited significantly improved biological performance as corneal substitute by harnessing a fast re-epithelialization and stromal regeneration potential.